Molecular Pathogenesis of Chronic Myelomonocytic Leukemia and Potential Molecular Targets for Treatment Approaches - Geissler, Klaus (Frontiers in Oncology, 2021)
Numerous examples in oncology have shown that better understanding the pathophysiology of a malignancy may be followed by the development of targeted treatment concepts with higher efficacy and lower toxicity as compared to unspecific treatment. The pathophysiology of chronic myelomonocytic leukemia (CMML) is heterogenous and complex but applying different research technologies have yielded a better and more comprehensive understanding of this diseae. At the moment treatment for CMML is largely resticted to the unspecific use of cytotoxic drugs and hypomethylating agents (HMA). Numerous potential molecular targets have been recently detected by preclinical research which may ultimately lead to treatment concepts that will provide meaningful benefits for certain subgroups of patients.